Peran Agent dalam Penerbitan Port Clearance Kapal Berbendera Asing pada Kantor KSOP oleh PT. Dalian Putra Maritim Cabang Belawan - Rati Fatria Putri; Dina Rispianti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The Port Clearance Certificate (PCC / SPB) is a mandatory state document issued by the Harbor Master (Syahbandar) as proof of the ship's seaworthiness and the fulfillment of all administrative obligations before leaving the port. In the clearance process for foreign-flagged vessels, the role of the shipping agent is crucial as the representative of the ship owner to coordinate all required permits and documents with various related government agencies (Harbor Master's Office/KSOP, Customs, Quarantine, and Immigration). PT. Dalian Putra Maritim Belawan Branch utilizes an integrated digital system (Inapornet) to manage ship agency services for both incoming and outgoing vessels. This study aims to comprehensively analyze and describe the role and effectiveness of the ship agent, PT. Dalian Putra Maritim Belawan Branch, in expediting the process of issuing the Port Clearance for foreign ships at the Harbor Master and Port Authority Office (KSOP) in Belawan. This research employs a qualitative-descriptive method supported by: 1) Library Research to collect theoretical data and regulations; and 2) Field Research, which involves direct observation of Standard Operating Procedures (SOPs) and the collection of accurate data within the Belawan Port environment. The research results indicate that the ship agent plays a central and vital role in the entire Port Clearance issuance process. The success of issuing the Port Clearance is heavily dependent on the speed, accuracy, and efficiency of the coordination carried out by the agent, ensuring that the vessel meets all safety, security, and maritime environmental protection requirements before being permitted to sail.